Modelagem de Sistemas Ambientais: integrando geotecnologias e geoestatística - Alesson Pires Maciel Guirra (2021)
Geotechnologies are important tools for spatial analysis, supporting the decision by allowing the analysis of environmental phenomena irregularly collected in geographic space. Therefore, in the first chapter it presents a bibliographic review on the use of geotechnologies applied to the planning of medium cities, consulting the database of Scopus journals. In the second chapter we discuss the implementation of a methodological routine to spatialize the intrinsic risk to contamination by pesticides in water bodies and to determine monitoring points, this routine is of low cost and aims to supply the lack of consistent hydrogeological data in certain regions of Brazil. The third chapter presents an optimization and application technique for the intrinsic vulnerability index of aquifers to the species (IVIAP), adapting and updating the routine for obtaining this index based on recent evidence on the infiltration and recharge of aquifers in the Cerrado biome. In the fourth chapter, we determine the best source of free, multispectral images of medium resolution to diagnose hydrodynamic processes in a tropical dam disturbance zone. In the fifth chapter, an integrative review on karst in Mato Grosso do Sul was carried out, evaluated as a geological-environmental attribute by location that conditions the occurrence of natural cavities, in addition to the possibility of predicting the number of cavities by simple and linear regression methods. and investigate whether there is spatial autocorrelation with some attributes. In the sixth and final chapter, the Empirical Model of Underground Water Potential (MEPHS) is explored, as well as the themes of associated elements in relation to emergences, cavities and springs, in addition to the application of the method for assessing vulnerability to aquifer contamination (GOD) , verifying its relationship with the MPHS. It is also proposed a method of estimating the static level from the MEPHS, the quota of the wells and the surface of the water level interpolated by the Spline method.